La dislexia fonológica y su incidencia en el rendimiento académico de los estudiantes de la escuela fiscal mixta Dr. Rodrigo Ugarte Córdova de la ciudad de Pasaje, período lectivo 2011-2012. - Erráez Loja, Ana Leonor (2012)
This paper deals with one of the specific learning disorders such as dyslexia, a problem that affects a large number of children at school age and now becomes much more worrying for the government's policy to achieve educational inclusion, without be prepared to face it.